Penerapan Algoritma VLBE Pada Aplikasi Penyimpanan File Secara Online - Sujanne Manalu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
In today's technological developments, information can be quickly found through increasingly rapidly developing technologies, such as the internet. Many people have files or data that they want to save into online applications. However, the large size of the data results in waste in the use of storage media and the process of sending data. To save those two things, data compression is needed. Data compression is the process of reducing the size of a data to produce a digital representation that is dense or compact but can still represent the quantity of information contained in the data. There are so many algorithms to compress existing data, but none of these algorithms is optimal in compressing text data. This research was conducted to reduce a file size before uploading it to the application using the VLBE (Variable Length Binary Encoding) algorithm. Variable Length Binary Encoding Algorithm is a data compression algorithm that encodes each character by sorting the characters by frequency and sorting stably to form a series of bits. The advantage of this VLBE algorithm is that the variable-length code can allow the source to be compressed with zero error and can be read back by Solomon symbols.